Scale for Measuring Gender Stereotypes: Construction and Preliminary Validation - Winiewski, Mikołaj; Majcher, Małgorzata; Marcinkowska, Karolina (Przegląd Psychologiczny, 2025)
Objectives: The aim of the study was to develop and preliminarily validate a new, psychometrically reliable tool for measuring contemporary gender stereotypes. The tool, based on a two-dimensional model of social perception, was adapted to the Polish context and designed to capture the dynamic nature of stereotypes, thereby filling the gap left by outdated instruments. Method: The process of creating the scale involved the generation of descriptors (traits) by a group of experts, followed by verification and selection of traits in an exploratory study (N = 309). Ultimately, 20 adjectives were selected for the tool. In the next two preliminary studies (N = 276 and N = 241), the structure of the tool was validated. Results: Analyses have shown that selected traits strongly differentiate the images of men and women. The new scale has a reliable and stable structure and appears to be a credible tool for measuring gender stereotypes. Conclusions: The tool presented in this article is a novel alternative to existing methods of measuring gender stereotypes in Poland. Preliminary validation confirms its reliability and usefulness, thus opening the way for further research into the dynamics and content of contemporary stereotypes.